What's social about social emotions? - Hareli, S; Parkinson, B (2008)
This paper presents a new approach to the demarcation of social emotions, based on their dependence on social appraisals that are designed to assess events bearing on social concerns. Previous theoretical attempts to characterize social emotions are compared, and their inconsistencies highlighted. Evidence for the present formulation is derived from theory and research into links between appraisals and emotions. Emotions identified as social using our criteria are also shown to bring more consistent consequences for social behavior than nonsocial emotions. We conclude by considering ways of validating and refining our classification. © 2008 The Executive Management Committee/Blackwell Publishing Ltd.